Climate stewardship : taking collective action to protect California - Merenlender, Adina Maya, 1963-; Buhler, Brendan (University of California Press, 2021)
"As climate disruption intensifies the world over, Californians are finding solutions across a diversity of communities and landscapes. Though climate change is a global existential threat, we cannot wait for nation states to solve the problem when there are actions we can take now to protect our own communities. In Climate Stewardship: Taking Collective Action to Protect California, readers are invited on a journey to discover that all life is interconnected and shaped by climate and how communities can help tackle climate change. Climate Stewardship shares stories from everyday people and shows how these actions enhance the resilience of communities and ecosystems across 10 distinct bioregions. Climate science that justifies these actions is woven throughout, making it easy to learn about Earth's complex systems. The authors interpret and communicate these stories in a way that is enjoyable, inspiring, and even amusing. California is uniquely positioned to develop and implement novel solutions to widespread climate challenges, owing to the state's remarkable biogeographic diversity and robust public science programs. Produced in collaboration with the UC California Naturalist Program, Climate Stewardship focuses on regenerative approaches to energy, agriculture, land and water use across forested, agricultural, and urban landscapes. Because of the hopeful and encouraging tone of the book, readers may also develop a sense that they, too, can act now to make meaningful change in their communities"--